Hope When it Appears Hopeless: A Review of Need for Surgical Decompression in Severe TBI Patients with Fixed Dilated Pupils - Narkhede, Tejas; Kaul, Rakshay; Yadav, Sarvesh; Meena, Rajesh; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
The Glasgow Coma Scale (GCS) score of 3, the lowest on the scale, traditionally indicates a deep coma with poor prognosis and has often been considered a marker of futile care in traumatic brain injury (TBI). This perception, particularly when associated with bilateral fixed and dilated pupils (BFDP), has led to early decisions on limiting or withdrawing treatment.This case series is studied to revisit and reevaluate the need for surgical decompression in patients who has a GCS of 3 with fixed dilated pupils and to understand if such patients can be given a chance when the prognosis appears dismal.We present a case series of three patients with GCS 3 and BFDP who underwent timely neurosurgical intervention. All three cases defied conventional prognostic expectations, achieving meaningful neurological recovery. Additionally, we reviewed the existing literature on outcomes in this patient subset.Despite initial presentations suggestive of grave prognosis—including fixed pupils and large intracranial hemorrhages—early aggressive intervention (e.g., decompressive craniectomy, external ventricular drainage) resulted in progressive neurological improvement. All patients were discharged with GCS scores of E4VtM5 or higher, intact brainstem reflexes, and vital stability.While a GCS of 3 with BFDP is associated with high mortality, it should not be viewed as universally incompatible with survival or recovery. Our case series, supported by literature, underscores the need for individualized management and delayed prognostication. Early surgical intervention, particularly in younger patients, may yield favorable outcomes and should be considered before labeling such cases as futile.
Keywords: decompression; decompressive craniectomy; fixed dilated pupils; GCS E1V1M1; GCS E1VtM1; severe TBI; severe traumatic brain injury